2009
DOI: 10.1152/ajpcell.00523.2008
|View full text |Cite
|
Sign up to set email alerts
|

FXYD1 phosphorylation in vitro and in adult rat cardiac myocytes: threonine 69 is a novel substrate for protein kinase C

Abstract: FXYD1 (phospholemman), the primary sarcolemmal kinase substrate in the heart, is a regulator of the cardiac sodium pump. We investigated phosphorylation of FXYD1 peptides by purified kinases using HPLC, mass spectrometry, and Edman sequencing, and FXYD1 phosphorylation in cultured adult rat ventricular myocytes treated with PKA and PKC agonists by phosphospecific immunoblotting. PKA phosphorylates serines 63 and 68 (S63 and S68) and PKC phosphorylates S63, S68, and a new site, threonine 69 (T69). In unstimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
112
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(125 citation statements)
references
References 34 publications
11
112
0
2
Order By: Relevance
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 52%
See 1 more Smart Citation
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 52%
“…We have found the ␤ 3 adrenergic receptor mediates stimulation of the Na ϩ -K ϩ pump in cardiac myocytes (5). 5 We, therefore, used forskolin, as have most of the recent studies (7,11,12,15,16).…”
Section: Namentioning
confidence: 99%
“…Drugs, Antibodies, and Chemicals-Antibodies to the PLM N terminus (raised in chickens) and PLM phosphorylation sites (raised in sheep) are described elsewhere (4,6). Anti-phospholamban raised in mice was from Millipore, and anti-caveolin 3 raised in mice was from BD Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…In cardiac myocytes, the sodium pump associates with FXYD1 (phospholemman (PLM) 3 ) (3,4), which was first recognized as an abundant phosphoprotein in the cardiac sarcolemma (5). Acute regulation of the cardiac sodium pump by the adrenergic system is through phosphorylation of PLM (4, 6 -10), which is unique in the FXYD family in having multiple phosphorylation sites on its intracellular C terminus (6,11). Unphosphorylated PLM inhibits the cardiac sodium pump by reducing its sodium affinity (8 -10, 12) and V max (4,6,7,13), and phosphorylation of PLM by PKA (on serine 68) or PKC (on serines 63 and 68 and threonine 69) relieves this inhibition (8,9) and in some models actually increases V max of the pump (4,10,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation